The Proyecto Costa Escondida: Recent interdisciplinary research in search of freshwater along the North Coast of Quintana Roo, Mexico. (19th July 2016) - Beddows, Patricia A.; Glover, Jeffrey B.; Rissolo, Dominique; Carter, Alice M.; Jaijel, Roy; Smith, Derek M.; Goodman‐Tchernov, Beverly
Abstract : Access to potable water has always been a major concern for human settlement, and this is particularly acute in coastal areas where freshwater can be compromised by saline marine waters. The northeast portion of Mexico's Yucatan Peninsula has a massive freshwater aquifer that today supports the international tourist destinations of Cancun and the Riviera Maya. However, access to this aquifer in pre‐Columbian times was restricted to natural features, such as cenotes (limestone sinkholes), aguadas (freshwater ponds), and coastal springs, or cultural features like wells, the viability of which is directly linked to sea level, which has risen over 2 m in the past 3000 years. In addition, ancient Maya inhabitants of the Yucatan collected rainwater in reservoirs, smaller‐scale cisterns called chultunes, or in ceramic pots. At the coastal site of Vista Alegre, located on the north coast of the Peninsula, there is limited evidence of potable water collection strategies, which has led members of the Proyecto Costa Escondida to critically examine how the freshwater access at the site changed over the past three millennia. To do this, the interdisciplinary research team has conducted (1) a physico‐chemical characterization of accessible surface and groundwater using a calibrated multiparameter probe, (2) a multiproxy study (i.e., micropaleontology, oxygen isotopic analysis) from 12 manual push cores taken in the waters surrounding Vista Alegre, and (3) an archaeological investigation. We hope our project serves as a model for future projects that strive to understand the complex and dynamic relationships between past peoples and their coastlines. WIREs Water 2016, 3:749–761. doi: 10.1002/wat2.1161 This article is categorized under: Engineering Water > Planning Water Science of Water > Water and Environmental Change Human Water > Water Governance